Kajian Rintis Penilaian Literasi Digital : Kesediaan Guru Prasekolah Menggunakan Platform Pembelajaran dalam Talian untuk Pendidikan Pemakanan = (A Pilot Study Assessing Digital Literacy: Preschool Teachers’ Readiness to Use Online Learning Platforms in Nutrition Education) - Chong, Yi Ting; Poh, Bee Koon; Ruzita, Abdul Talib; Koh, DENISE; Woo, Pik Xuan; Nelson, Georgia Livan; Cheah, Whye Lian; Julia Ai Cheng, Lee; Noor Hafizah, Yatiman; Cecilia A., Essau; Sue, Reeves; Carolyn, Summerbell; et al. (Universiti Kebangsaan Malaysia, 2024)
eToyBox is a learning management system for preschool teachers to improve their health literacy, which ultimately aims to improve children’s obesity-related behaviour. As part of the development process of eToyBox, assessment on digital literacy, acceptance of digitization of education materials, and perceived barriers in adopting online learning is needed. Fifty-four preschool teachers under the Community Development Department (KEMAS) in Kuala Lumpur, Selangor, and Sarawak, who participated in ToyBox Study Malaysia intervention in 2018, took part in this cross-sectional study. An online self-administered questionnaire was used to assess sociodemographic background, use of communication tools and media, and teacher’s views on adapting the ToyBox modules to digital education materials. Respondents were contacted, and questionnaire link was shared through WhatsApp messages. Most participants (74.0%) were Malay females aged 31 to 40 years old. Most participants had internet access (94.4%) and owned at least a smart phone, laptop or tablet (94.4%). Participants perceived their computer skills to be average (75.0%). Majority of respondents (65.0%) reported advanced and higher abilities in word processing and email, but only 22.0% in spreadsheet skills. The main barrier to accessing online material was unstable internet connection (74.1%). Most respondents (90.0%) agree that adapting effective modules to online learning will be beneficial for professional development and teaching practices. In conclusion, most participants supported digitizing Toybox Study Malaysia educational content and were comfortable 72 with its implementation via an online learning platform. The findings from this study can advise future development of online learning materials for preschool teachers in Malaysia.